Survei Sarana dan Prasarana Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan pada Sekolah Menengah Pertama di SMP Bhakti Praja Kebumen - Mokhamad Parmadi; Heri Yulianto (Jurnal Syntax Admiration, 2024)
The focus of this research is how the condition of Sports Physical Education learning facilities and infrastructure at Smp Bhakti Praja Kebumen. The purpose of this study is to determine the condition of the facilities and infrastructure in Smp Bhakti Praja Kebumen meets the standards or not.This research uses qualitative methods, because it aims to describe the availability of Sports Physical Education learning facilities and infrastructure through rationalization of the number of existing facilities and infrastructure with the needs in learning. Data collection is carried out using documentation and observation. The research instrument is in the form of an observation sheet on the availability of sports facilities and infrastructure. Data analysis in this study includes quantitative data, namely the number of sports facilities and infrastructure.